An integrative theoretical model of public support for ex-offender reentry - Rade, Candalyn B. (International journal of offender therapy and comparative criminology, 2018)
Prior research suggests that public and ex-offender characteristics are associated with attitudes toward ex-offenders and support for their reentry; however, research examining reasons for these associations is limited. Research also is limited on the association between attitudes toward ex-offenders generally, and support for their reentry, specifically. Implicit theory offers a new approach to explaining public attitudes through beliefs in the fixed or malleable nature of people (i.e., mindsets). We developed and tested an integrative model applying implicit theory to investigate mechanisms through which beliefs explain support for reentry. Results showed that growth mindsets predicted more positive attitudes toward ex-offenders, which, in turn, predicted greater support for reentry. Belief in a just world, prior contact with an ex-offender, and political orientation were among the covariates of reentry support. Beyond supporting the application of implicit theory in this context, findings suggest that anti-stigma interventions should target growth mindsets to promote community reintegration.